Breast cancer screening beliefs by practice location - Lawvere Silvana; Mahoney Martin C; Santora Lisa M; Englert Jessica J; Symons Andrew B; Mirand Amy L (BMC, 2003)
Abstract Background This study examines variations in breast cancer screening among primary care clinicians by geographic location of clinical practice. Methods A cross-sectional survey design was used to examine approaches to breast cancer screening among physicians, nurse practitioners, and physician assistants involved in primary care practice. A summary index of beliefs about breast cancer screening was created by summing the total number of responses in agreement with each of four survey items; values for this summary variable ranged between zero and four. Respondents were classified into urban, rural and suburban categories based upon practise location. Results Among the 428 respondents, agreement with "correct" responses ranged from 50% to 71% for the individual survey items; overall, half agreed with three or more of the four breast cancer screening items. While no significant differences were noted by practice location, variation in responses were evident. Reported use of written breast cancer guidelines was less in both suburban (OR = 0.51) and urban areas (OR = 0.56) when compared to clinicians in rural areas. Conclusion Development of an evidence-based consensus statement regarding breast cancer screening would support a single set of unambiguous guidelines for implementation in all primary care settings, thus decreasing variations in how breast cancer screening is approached across varied clinical settings.